Effect of heat treatment on the physico-chemical properties of starch from different botanical sources - Mohd Adzahan, Noranizan; Mat Hashim, Dzulkifly; Abdul Rahman, Russly (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Changes in the physicochemical properties of wheat, sago, tapioca and potato starches were studied after heating for 1 hour at 100°C, 110°C, and 120°C and for 2 hours at 120°C. These properties were characterised through the swelling behaviour of starch granules, amount of carbohydrate materials leached from the granules, starch paste retrogradation rate and gel strength. For all starches except wheat, the swelling ability, rate of retrogradation and gel strength decreased while solubility increased with increasing temperature and heating time. Wheat starch followed this pattern only when heated at 120°C for 1 and 2 hours. Gel strength correlated well with the ratio of amylose to amylopectin (R) in the leachate. To produce fried crackers with good expansion properties, the granule has to be sufficiently degraded so as to allow more amylopectin to be leached out to achieve R value of 0.25-0.5. This can be achieved by heating wheat starch at 120°C for 1 hour or longer.